Уточнение структуры водород-вакансионных комплексов в титане методом Ритвельда - Абзаев Ю. А. Юрий Афанасьевич; Лидер А. М. Андрей Маркович; Клименов В. А. Василий Александрович; Лаптев Р. С. Роман Сергеевич; Бордулёв Ю. С. Юрий Сергеевич; Садритдинова Г. Д. Гульнара Долимжановна; Михайлов А. А. Андрей Анатольевич; Захарова М. А. Маргарита Анатольевна (2016, 2016)
Заглавие с экрана